EFL Student Teachers' Experiences in Writing Their Undergraduate Theses in Jambi - Abrar, Mukhlash; Fajaryani, Nunung; Hutabarat, Roni Rizki; Failasofah, Failasofah; Masbirorotni, Masbirorotni (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2023)
The purpose of this qualitative study was to comprehensively investigate the experiences in writing undergraduate theses, the challenges faced, and strategies to alleviate the encountered challenges, of ten EFL student teachers at one higher education institution in Jambi. To collect the data, we employed semi-structured interviews guided by an interview protocol to elicit the participants’ responses. The results of the study, through thematic analysis (Braun & Clark, 2006), indicated that there are four major themes of challenges in writing an undergraduate thesis, including linguistics and writing knowledge issues, psychological issues, media and resources issues, and supervision and time management issues. To cope with those challenges, the participants employed some strategies, such as self-management strategy, technological help, and help from others. This study suggests EFL student teachers identify issues they struggle with in writing their theses. It is necessary so they could find a helpful way to deal with the challenge.